2010
DOI: 10.1007/s10750-010-0518-y
|View full text |Cite
|
Sign up to set email alerts
|

The expression pattern of dormancy-associated genes in multiple life-history stages in the rotifer Brachionus plicatilis

Abstract: Rotifer resting eggs retain their viability for several decades in a non-desiccated form and are of interest in discerning the processes associated with dormancy, since in most organisms this phenomenon is linked with desiccation. The expression pattern of candidate genes with biological functions associated with dormancy in several other organisms was examined in rotifers. High-throughput transcriptome profiling revealed three patterns of gene expression in resting eggs: (1) relatively highly expressed genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 57 publications
(67 reference statements)
1
35
0
Order By: Relevance
“…Smith et al review existing knowledge on the hsp stress proteins and using a variety of molecular tools show that stress proteins hsp 40 , 60 , and 70 are required for thermal tolerance in Brachionus manjavacas . Further, Denekamp et al note that diapausing embryos express genes for low molecular weight hsps . Unlike in other species that enter anhydrobiosis, desiccation tolerance in bdelloid rotifers is not dependent on production of the stabilizing sugar trehalose , and in fact several species lack the genes encoding these sugars .…”
Section: Temporary Waters: Contributions Of Rotifer Research To Ecolomentioning
confidence: 99%
See 1 more Smart Citation
“…Smith et al review existing knowledge on the hsp stress proteins and using a variety of molecular tools show that stress proteins hsp 40 , 60 , and 70 are required for thermal tolerance in Brachionus manjavacas . Further, Denekamp et al note that diapausing embryos express genes for low molecular weight hsps . Unlike in other species that enter anhydrobiosis, desiccation tolerance in bdelloid rotifers is not dependent on production of the stabilizing sugar trehalose , and in fact several species lack the genes encoding these sugars .…”
Section: Temporary Waters: Contributions Of Rotifer Research To Ecolomentioning
confidence: 99%
“…Unlike in other species that enter anhydrobiosis, desiccation tolerance in bdelloid rotifers is not dependent on production of the stabilizing sugar trehalose , and in fact several species lack the genes encoding these sugars . Late embryogenesis abundant (LEA) proteins and multiple copies of alpha tubulin appear to be important in desiccation tolerance. In addition, ability to recover from anhydrobiosis is dependent on time and other environmental conditions.…”
Section: Temporary Waters: Contributions Of Rotifer Research To Ecolomentioning
confidence: 99%
“…The ecological significance of dormancy in rotifers has been extensively reviewed (36 -41) and molecular information was published in recent years (42)(43)(44)(45)(46)(47)(48)(49)(50)(51). Including, the expression patterns in amictic and resting eggs of genes encoding proteins with putative functions in dormancy (52,53; e.g. small heat-shock proteins, ferritin, glutathione-S-transferase, and trehalose-6-phosphate synthase).…”
mentioning
confidence: 99%
“…Real time RT-PCR showed that LEA proteins and small heat shock proteins (sHSP) were upregulated in both resting eggs and females producing resting eggs in comparison to amictic eggs and females producing amictic eggs, respectively [6]. High-throughput Illumina sequencing data in concurrence to RT-PCR analysis showed higher expression of LEAs, glutathione-S-trasnferases, HSPs, and downregulation in trehalose metabolism, aquaporins transcription during early RE dormancy and the respective expression pattern for the aforementioned genes in females carrying REs versus amictic correlated with the types of eggs they produced [7]. Highthroughput Illumina sequencing was also used to show that for resting eggs, genes associated with cellular maintenance and survival were upregulated such as antioxidants, oxidoreductases, and protein chaperone genes; in comparison to amictic eggs, genes associated with cellular and organismic development such as cell cycle and cytoskeletal genes [8].…”
Section: Genetic Screening Of Genes Involved In Dormancymentioning
confidence: 90%